Active targeted Janus nanoparticles enable anti-angiogenic drug combining chemotherapy agent to prevent postoperative hepatocellular carcinoma recurrence. (February 2022) - Zhang, Xiu-Ping; Chen, Xiang-Jun; Li, Bo-Zhao; Xu, Shuai; Wu, Zhou-Liang; Hu, Ming-Gen; Zhao, Zhi-Ming; Zhao, Guo-Dong; Wang, Chang-Rong; Hong, Wei; Li, Su-Ping; Li, Lu; et al.
Abstract: Surgery is one of the main effective strategies for the treatment of solid tumors, but high postoperative recurrence is also the main cause of death in current cancer therapy. The prevention of postoperative hepatocellular carcinoma (HCC) recurrence is a clinical problem that needs to be solved urgently. At present, there are still some problems to be solved, such as, how to achieve free drugs to target the site of surgical resection; develop a strategy for the simultaneous administration of multiple drugs to inhibit postoperative recurrence; and provide the appropriate animal model that mimics the process of postoperative HCC recurrence. In this study, we used a facile and reproducible method to successfully prepare amphiphilic Janus nanoparticles (JNPs). In order to improve targeting of the JNPs to residual HCC cells after surgery, we modified the side of gold nanorods (GNRs) with lactobionic acid (LA), thus creating LA-JNPs. This provided an active and targeted co-delivery system for hydrophilic and hydrophobic drugs in separate rooms, thus avoiding mutual effects. Next, we established two models to simulate postoperative HCC recurrence: a subcutaneous postoperative recurrence model based on patient-derived tumor xenograft (PDX) tissues and a postoperative recurrence model of orthotopic HCC. By applying these models, the enhanced permeability and retention effect (EPR) based tumor targeting and LA based active targeting can jointly promote the enrichment and uptake of JNPs at tumor site. LA-JNPs represented an efficient targeting system for the co-delivery of Sorafenib/Doxorubicin with an optimized anti-recurrence effect and significantly improved the survival of mice during treatment for postoperative recurrence.